The onset of convection in a binary nanofluid saturated porous layer. (1st January 2012) - Yadav, Dhananjay; Agrawal, G.S.; Bhargava, Rama
The double-diffusive convection in a horizontal nanofluid saturated porous layer is studied analytically using a Brinkman-Darcy model. The model used for nanofluid includes the effects of Brownian motion and thermophoresis. The linear stability theory is employed to obtain the condition for the onset of convection. The effect of solute Rayleigh number, Soret parameter, Dufour parameter, Lewis number, nanoparticle Rayleigh number, nanoparticle Lewis number, modified particle-density increment parameter, modified diffusivity ratio, Darcy number and the porosity parameter have been analysed on the onset of convection. The sufficient conditions for the non-existence of overstability are also obtained.